Tunable apodizers and tunable focalizers using helical pairs - Ojeda-Castaneda, Jorge; Ledesma, Sergio; Gomez-Sarabia, Cristina Margarita (Photonics Letters of Poland, 2013)
We unveil the use of two helically distributed amplitude masks for controlling the damping coefficient of Gaussian-like windows. We show that by introducing an in-plane rotation between the members of the proposed pair, one eliminates the polar dependence of the masks. Then, one can tune the half-width of radial Gaussian-like apodizers. In a similar manner, we show that if one uses two helically distributed refractive elements, as a pair, then one can control the maximum value of the optical path difference; which is useful for tuning several radial focalizers. Full Text: PDF References W. T. Welford, "Use of Annular Apertures to Increase Focal Depth", J. Opt. Soc. Am. 50, 749-753 (1960). CrossRef J. Ojeda-Casta-eda, L. R. Berriel Valdos and E. L. Montes, "Line-spread function relatively insensitive to defocus", Optics Letters, Vol. 8, No. 8, 458-460 (1983). CrossRef J. Ojeda-Casta-eda, L. R. Berriel-Valdos and E. Montes, "Bessel annular apodizers: imaging characteristics", Appl. Opt. 26, 2770-2772 (1987). CrossRef E. R. Dowski, T. W. Cathey, "Extended depth of field through wave-front coding", Appl. Opt. 34, 1859-1865 (1995). CrossRef Angel Sauceda and J. Ojeda-Castaneda, "High focal depth with fractional-power wave fronts", Opt. Lett. 29, 560-562 (2004). CrossRef Albertina Castro and J. Ojeda-Castaneda, "Asymmetric Phase Masks for Extended Depth of Field", Appl. Opt. 43, 3474-3479 (2004). CrossRef S. Mezouari, G. Muyo, A. R. Harvey, "Circularly symmetric phase filters for control of primary third-order aberrations: coma and astigmatism", J. Opt. Soc. Am. A 23, 1058-1062 (2006). CrossRef G. Mikuła, Z. Jaroszewicz, A. Kolodziejczyk, K.Petelczyc and M. Sypek, "Imaging with extended focal depth by means of lenses with radial and angular modulation", Opt. Exp. 15, 9184-9193 (2007). CrossRef J. Ojeda-Castaneda, J. E. A. Landgrave and C. M. Gómez-Sarabia, "Conjugate phase plate use in analysis of the frequency response of imaging systems designed for extended depth of field", Appl. Opt. 47, E99 – E105 (2008). CrossRef J. Ojeda-Castaneda, E. Yépez-Vidal, E. García-Almanza and C. M. Gómez-Sarabia, "Tunable Gaussian mask for extending the depth of field", Photonics Letters of Poland, Vol. 4 (3), 115-117 (2012). DirectLink W. T. Plummer, J. G. Baker and J. van Tassell, "Photographic Optical Systems With Nonrotational Aspheric Surfaces", Appl. Opt. 38, 3572-3592 (1999). CrossRef I. Kitajima, British Patent 250, 268 (July 29, 1926). H. J. Birchall, U. S. Patent 2,001, 952 (may 21, 1935). A. W. Lohmann, British Patent 998, 191 (May 29, 1964). A. W. Lohmann, Republic Française 1, 398, 351 (June 10, 1964). A. W. Lohmann, Italy 727,848 (June 19, 1964). A. W. Lohmann, "A New Class of Varifocal Lenses", Appl. Opt. 9, 1669-1671 (1970). CrossRef L. W. Alvarez, U. S. Patent 3, 305, 294 (February 21, 1967). L. W. Alvarez and W. E. Humphrey, U. S. Patent 3, 507, 565 (April, 21, 1970). A. W. Lohmann, IBM Technical Disclosure Bulletin 10, 407-411 (1967). A. W. Lohmann, "Variable Fresnel Zone Pattern", Appl. Opt. 6, 1567-1570 (1967). CrossRef K. Crabtree, J. A. Davies and I. Moreno, "Optical Processing with Vortex-Producing Lenses", Appl. Opt.43, 1360-11367 (2004). CrossRef J. H. McCleod, "The Axicon: A New Type of Optical Element", J. Opt. Soc. Am. 44, 592-597 (1954). CrossRef N. Davidson, A. A. Friesem and E. Hasman, "Holographic axilens: high resolution and long focal depth", Opt. Lett. 16, 523-525 (1991). CrossRef G. Mikuła, Z. Jaroszewicz, A. Kolodziejczyk, K.Petelczyc and M. Sypek, "Imaging with extended focal depth by means of lenses with radial and angular modulation", Opt. Exp. 15, 9184-9193 (2007). CrossRef